Food label and packaging survey of children's baked snack foods in the Philippines - Uy, Jacquelyn Salve; Rumbaoa, Rowena Grace O. (Quezon City College of Home Economics, 2007)
ABSTRACT The main interest of the study is to examine food labels of baked snack foods available to children by utilizing a survey method. Baked snack products belonging to the cakes and cookies category are the subjects of the study. Based on the evaluation of packaging and labels of the snack products involved in the study, majority of the manufacturers complied with the mandatory labeling requirements established by BFAD. Majority (95%) of the products surveyed also contain nutrition panels. The samples were also evaluated based on ingredients and food additives. The food additives used by manufacturers are classified as safe for consumption.
Thesis (BSFT)--University of the Phuilippines Diliman.
Keywords: Food -- Packaging -- Philippines; Food -- Labeling -- Philippines; Snack foods; Baked products